Distributed Computing and Artificial Intelligence, Special Sessions II - Intelligent Systems Applications, 20th International Conference - Jove, Esteban; Zayas-Gato, Francisco; Michelena, Álvaro; Calvo-Rolle, José Luis (Lecture Notes in Networks and Systems,, 2023)
XII, 83 p. 23 illus., 22 illus. in color.